Farmaceutické amorfní hydráty - Kratochvíl, Bohumil; Koupilová, Iva (Chemické listy, 2011)
A new item of amorphous hydrates was recently introduced into a group of active pharmaceutical ingrediences. Their concept has a realistic content, but it is strongly influenced by the patent policy of pharmaceutical companies claiming possible new phases. An amorphous hydrate can be defined as a metastable, water-saturated amorphous phase, which retains a constant amount of water for a long time. Due to their advantageous properties, amorphous hydrates can be used for drug formulation in pharmacy.
Keywords: voda; Pharmaceutical Preparations; Crystallization; molekulární struktura; farmaceutická technologie; financování organizované; Technology, Pharmaceutical; krystalizace; léčivé přípravky; Molecular Structure; Water; rozpustnost; Phase Transition; Financing, Organized; Chemistry, Pharmaceutical; farmaceutická chemie; změna skupenství; Solubility